Enhancement of visible light photocatalytic hydrogen evolution by bio-mimetic C-doped graphitic carbon nitride - Mohamad Saufi Rosmi (Tanjong Malim, 2019)
Enhancement of visible light photocatalytic hydrogen evolution by bio-mimetic C-doped graphitic carbon nitride by Mohamad Saufi Rosmi